Effects of irradiation temperature and dose rate on the mechanical properties of self-ion implanted Fe and Fe-Cr alloys - Hardie, C; Williams, C; Xu, S; Roberts, S (Elsevier, 2013)
Pure Fe and model Fe-Cr alloys containing 5, 10 and 14%Cr were irradiated with Fe+ ions at a maximum energy of 2 MeV to the same dose of 0.6 dpa at temperatures of 300 C, 400 C and 500 C, and at dose rates corresponding to 6 × 10-4 dpa/s and 3 × 10-5 dpa/s. All materials exhibited an increase in hardness after irradiation at 300 C. After irradiation at 400 C, hardening was observed only in Fe-Cr alloys, and not in the pure Fe. After irradiation at 500 C, no hardening was observed in any of the materials tested. For irradiations at both 300 C and 400 C, greater hardening was found in the Fe-Cr alloys irradiated at the lower dose rate. Transmission electron microscopy and atom probe tomography of Fe 5%Cr identified larger dislocation loop densities and sizes in the alloy irradiated with the high dose rate and Cr precipitation in the alloy irradiated with the low dose rate.